The Comparison of Streptococcus agalactiae Isolated from Fish and Bovine using Multilocus Sequence Typing - ANGELA MARIANA LUSIASTUTI; HELGA SEEGER; AGUSTIN INDRAWATI; MICHAEL ZSCHÖCK (Bogor Agricultural University, Indonesia, 2013)
Multilocus sequence typing (MLST) has greater utility for determining the recent ancestral lineage and the relatedness of individual strains. Group B streptococci (GBS) is one of the major causes of subclinical mastitis of dairy cattle in several countries. GBS also sporadically causes epizootic infections in fish. The aim of this study was to compare the evolutionary lineage of fish and bovine isolates in relation to the S. agalactiae global population as a whole by comparing the MLST profiles. Twenty S. agalactiae isolates were obtained from dairy cattle and fish. PCR products were amplified with seven different oligonucleotide primer pairs designed from the NEM316 GBS genome sequence. Clone complexes demonstrated that bovine and fish isolates were separate populations. These findings lead us to conclude that fish S. agalactiae is not a zoonotic agent for bovine. MLST could help clarify the emergence of pathogenic clones and to decide whether the host acts as a reservoir for another pathogenic lineage.